Clinical manifestaions of renal disease in patients with tuberous sclerosis complex at University Medical Centre Maribor: Klinične značilnosti in ledvična prizadetost bolnikov s tuberozno sklerozo v UKC Maribor - Golob Jančič, Sonja; Gradišnik, Peter; Osterc Koprivšek, Andreja; Gačnik, Albin; Marčun Varda, Nataša (Acta Medico-Biotechnica, 2022)
Purpose: Tuberous sclerosis is an autosomal dominant neurocutaneous syndrome that affects approximately 1/6000–10,000 people. The clinical presentation varies and is dependent on patient age. Renal manifestations, most often angiomyolipomas, cystic renal disease, and renal carcinoma, are present in 48%–80% of patients with tuberous sclerosis. The aim of our study was to determine the clinical characteristics and extent of renal impairment in patients with tuberous sclerosis who were followed at the University Medical Centre Maribor.Methods: We reviewed the medical records of patients with tuberous sclerosis (ICD Q85.1) who received care at the University Medical Centre Maribor. The medical history, clinical characteristics, laboratory results, imaging studies, and current treatment were highlighted. In addition, the results of genetic analysiswere reviewed.Results: Our cohort consisted of 13 patients with tuberous sclerosis (age range, 7–71 years; median age, 16 years; average age, 25.2 [14.6-35.9] years). Cutaneous pathology was noted in 12 (92%) patients. Renal manifestations were present in 6 (60%) of the patients; 46% had angiomyolipomas and 23% had renal cysts. No significant renal function impairment was demonstrated. Two patients were treated with systemic everolimus and two patients were treated with topical everolimus for skin lesions. Genetic analysis was performed in seven patients, five of whom were positive and two of whom were negative.Conclusion: In agreement with literature reports, our results confirmed that renal impairment frequently occurs in tuberous sclerosis patients; however, because most of our patients were children, renal function was stable and treatment was rarely needed. Regular screening and follow-up evaluations in the multidisciplinary team are essential for good long-term outcomes.
Keywords: tuberous sclerosis, kidney, angiomyolipomas, kidney cysts